Assessing cultural ecosystem services in the Hara mangrove forests: indicators for sustainable management in a Middle Eastern coastal marine protected area - Parvaneh Sobhani; Afshin Danehkar; Azade Deljouei; Marina Viorela Marcu; Seyed Mohammad Moein Sadeghi (Ecological Indicators, 2025)
Hara Coastal Marine Protected Area (CMPA) in southern Iran contains the largest mangrove ecosystem in the Middle East, providing essential Cultural Ecosystem Services (CESs) and supporting biodiversity conservation. Despite its ecological and socio-cultural significance, increasing human pressures and inadequate infrastructure threaten its sustainability. This study evaluates CES perceptions among local communities and tourists, identifying priority recreational activities, perceived barriers, and site-specific stressors using integrated social and ecological indicators. Findings reveal a strong dependence of local communities on the Hara CMPA, demonstrating high place attachment and a commitment to conservation. In contrast, tourists showed lower ecological awareness, valuing aesthetic and recreational experiences over conservation concerns. Natural features such as mangrove forests, tidal zones, and wildlife habitats were most valued, whereas human-modified sites like docks and historical villages were considered as less important. Infrastructure deficiencies and lack of suitable facilities emerged as the most significant barriers to CES utilization. Among CES categories, aesthetic values ranked highest, while educational values received the least recognition. To support sustainable management of the Hara CMPA, targeted strategies should enhance environmental awareness, upgrade infrastructure, and incorporate local knowledge in planning. The findings provide a set of ecological and social indicators to inform coastal policy, emphasizing the need for inclusive, stakeholder-centered approaches to balance conservation and human activities in marine protected area governance.